Values crisis and the role of basic stage social and national textbooks in facing it from the Jordanian teachers point of view - Al- Hazaime, Lubna Mohammad Khalaf; Al- Qauod, Ibrahim Abdulqadir (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to identify the role of basic stage national and social education textbooks in facing values crisis in Jordan. To achieve the aim of the study، the researchers developed a questionnaire as the validity and reliability of this questionnaire was established. The sample of the study consisted of (97) teachers selected using stratified random sampling from Qasabet Irbid Educational Directorate. The results of the study indicated low and moderate levels of religious، social، national، political، economic and aesthetic values inclusion in basic stage national and social education textbooks. The study recommended that there is a need for future research examining the values crisis and the role of school textbooks in facing them.
Keywords: Values; Values Crisis; Social and National Education Textbooks; Basic Stage